KAPASITAS AKSIAL-LENTUR KOLOM BERTULANGAN BAMBU WULUNG DENGAN TAKIKAN TIDAK SEJAJAR - Budhi Triyana; Agus Setiya Budi; Antonius Mediyanto (Program Studi Teknik Sipil FT UNS, 2014)
Residential development due to the rapid population constantly increases, triggering the prices of building materials, especially steel concretereinforcing growing up and experiencing scarcity, making it very burdensome to lower middle class society. To overcome this, then look for a newalternative materials as a substitute for steel reinforcement is using a reinforcement of bamboo slats. This study aims to determine the axial-flexuralcapacity of concrete columns reinforced wulung bamboo with parallel notches when compared to axial-flexural capacity of concrete columns steelreinforced and axial-flexural capacity of the columns without reinforcement.This study uses an experimental method with a total of 7 samples objects. The experimental thing used in this research is a concrete blockmeasuring 150 x 150 x 1500 mm. The two columns using plain steel reinforcement, two columns not using any reinforcement and three othersusing plain wulung bamboo not parallel notches. The quality of concrete is planned fc'= 15 MPa. Bending test performed at 28 days with thirdpointloading method.Testing is done by testing the axial-flexural capacity of the column using a loading frame, the eccentricity of the axial load of200 mm from the axis of the column.Based on the test results, the average value of the maximum axial load of the column reinforcement wulung bamboo not parallel notches is 22,833N. The Average value of the maximum flexural capacity of the column reinforcement wulung bamboo not parallel notches is 4,921,567 N.mm.The average value of the maximum axial load of the steel reinforcement column is 36,500 N. The Average value of the maximum flexuralcapacity of the steel reinforcement column is 8,132,600 N.mm. The average value of the maximum axial load of unreinforced column is 10,750N. The Average value of the maximum flexural capacity of unreinforced column is 2,157,955 N.mm. Based on the value of the maximumflexural capacity, the concrete columns reinforcement wulung bamboo not parallel notches can increase the flexural capacity of the column about56.153 % when compared with unreinforced concrete columns.